AN ANALYSIS ON FISHERY CAPTURE LICENSING TOWARD THE REGISTRATION AND MARKING OF FISH-TRANSPORTING VESSELS WITHIN THE SOUTH KALIMANTAN PROVINCE AUTHORITY - Amalia, Siti Dian (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2017)
This study aimed to (1) identify the distribution of fish-transporting vessels under the authority of South Kalimantan Province; (2) to analyze the causes of unregistered and unmarked fish-transporting vessels within the provincial authority; and (3) to analyze the causes of fishery capture licensing that continues to run without a Fishing Vessel Book (Buku Kapal Perikanan – BKP). This research activity was conducted at the Banjarmasin Fishing Port, Pelambuan Village, Banjarmasin Barat District, Banjarmasin City, South Kalimantan, with the fish-transporting vessel’s owners within the South Kalimantan authority as the research object. The data collected were the data sourced directly from the observation result in the research location, and other supporting data related to the research object. The results showed that the spreading of fish-transporting vessels that land their cargo at the Banjarmasin Fishing Port were found in Kotabaru Regency, Tanah Bumbu Regency, Tanah Laut Regency, Banjar Regency, Barito Kuala Regency, and Banjarmasin City. Based on the data, there are 183 fish-transporting vessels within South Kalimantan Province authority, but only 42 vessels or 23% ships that are registered as fishing vessels. While for the marking of the vessels, 100% have not carried out marking as fishing vessels. This is due to the unavailability of a standard BKP and the lack of understanding from the vessel owners. The Licensing of Fishery Capture in the form of SIUP and SIKPI is still issued by BPTSP using only recommendation from Department of Fisheries and Maritime Affairs of South Kalimantan Province. The registration and marking of fish-transporting vessels of South Kalimantan Province Authority are not optimal due to the unavailability of a standard BKP that can be used as collateral so that a policy is needed from the local government in terms of budgeting funds for the procurement of BKP so that fish-transporting vessels in South Kalimantan Province can be registered and marked as Indonesian fishing vessels.